DOWRY DIFFERENTIATION AND SOCIAL MEANING IN MUSLIM COMMUNITIES: A STUDY OF CUSTOMARY AND ISLAMIC LAW IN TANJUNG PAUH - Karimi, Harmo; Yul, Widya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines the social meaning and legal interaction of dowry differentiation within Muslim communities in Tanjung Pauh, focusing on the relationship between customary law and Islamic law. While previous studies on dowry in Indonesia have largely emphasized normative or economic aspects, limited attention has been given to how legal pluralism operates in everyday social practices, particularly when customary norms introduce distinctions not explicitly regulated in Islamic jurisprudence. This research adopts an empirical legal approach with a qualitative descriptive design. Data were collected through semi-structured interviews with customary leaders, religious figures, village authorities, and community members, complemented by observation and document analysis. The findings indicate that dowry determination is governed by a collective and institutionalized customary system, in which virgins receive one gram of gold and widows receive half a gram. This differentiation is consistently applied and widely accepted as a cultural symbol reflecting marital experience rather than as a form of social inequality. From the perspective of Islamic law, the practice is considered permissible as it upholds the principles of mutual consent, fairness, and the absence of coercion. This study demonstrates that the interaction between customary law and Islamic law results in a form of normative convergence, where local traditions are accommodated within Islamic legal values. It contributes to the discourse on legal pluralism by highlighting that culturally embedded practices can function harmoniously without undermining gender dignity. Practically, the study provides insight into how community-based norms shape the implementation of Islamic family law in diverse social contexts.